WEAR-RESISTANCE OF CHROMIC CAST IRONS OF EUTECTIC COMPOSITION - K. E. Baranovskij; V. M. Iljushenko (Литьë и металлургия, 2009)
Casting of wear-resistant chrome cast irons in combined molds and iron chills is studied. Application of these ways of casting results in blending of carbides and increasing of hardness of castings.